Overexpression of the calpain-specific inhibitor calpastatin reduces human alpha-Synuclein processing, aggregation and synaptic impairment in [A30P]αSyn transgenic mice. (11th March 2014) - Diepenbroek, Meike; Casadei, Nicolas; Esmer, Hakan; Saido, Takaomi C.; Takano, Jiro; Kahle, Philipp J.; Nixon, Ralph A; Rao, Mala V.; Melki, Ronald; Pieri, Laura; Helling, Stefan; Marcus, Katrin; et al.
Abstract : Lewy bodies, a pathological hallmark of Parkinson's disease (PD), contain aggregated alpha-synuclein (αSyn), which is found in several modified forms and can be discovered phosphorylated, ubiquitinated and truncated. Aggregation-prone truncated species of αSyn caused by aberrant cleavage of this fibrillogenic protein are hypothesized to participate in its sequestration into inclusions subsequently leading to synaptic dysfunction and neuronal death. Here, we investigated the role of calpain cleavage of αSyn in vivo by generating two opposing mouse models. We crossed into human [A30P]αSyn transgenic (i) mice deficient for calpastatin, a calpain-specific inhibitor, thus enhancing calpain activity (SynCAST(−)) and (ii) mice overexpressing human calpastatin leading to reduced calpain activity (SynCAST(+)). As anticipated, a reduced calpain activity led to a decreased number of αSyn-positive aggregates, whereas loss of calpastatin led to increased truncation of αSyn in SynCAST(−). Furthermore, overexpression of calpastatin decreased astrogliosis and the calpain-dependent degradation of synaptic proteins, potentially ameliorating the observed neuropathology in [A30P]αSyn and SynCAST(+) mice. Overall, our data further support a crucial role of calpains, particularly of calpain 1, in the pathogenesis of PD and in disease-associated aggregation of αSyn, indicating a therapeutic potential of calpain inhibition in PD.